N02 Inflammatory bowel disease and pregnancy: the impact of education in knowledge and attitude of women in reproductive age; one-year follow-up study. (25th January 2019) - Tsavdaroglou, T; Mantzaris, G; Tsavdaroglou, A; Fotos, N; Brokalaki, H
Abstract: Background: Because inflammatory bowel disease (IBD) affects women in reproductive age, knowledge and beliefs about pregnancy must be assessed in those women. The aim of this study was to compare (a) knowledge level and beliefs about pregnancy before and after educational intervention and (b) the same parameters in the group of women who underwent this educational intervention to women who did not undergo training. Methods: Eligible were outpatient IBD women of reproductive age. After obtaining a consent, demographics, clinical data and current treatment were recorded and all patients were invited to complete (a) the Crohn's and Colitis Pregnancy Knowledge Score (CCPKnow), which categorised in poor (0–7), adequate (8–10), good (11–13) and very good (≥14) level and (b) a structured tool formed for this study which assessed pregnancy beliefs. Subsequently, patients were randomly distributed in two groups, control group (CG) and intervention group (IG). Women in IG received a face-to-face educational training regarding pregnancy, and were given an educational leaflet. Then, patients were followed in the IBD Clinic at 3, 6, and 12 months after baseline with clinical assessment, laboratory tests and filling the same questionnaires. Results: Overall, 43 and 39 women were allocated to the IG and CG, respectively (Table 1). Basic demographics and clinical characteristics. At baseline, both groups had poor knowledge. After educational program the level of Knowledge increased significantly in the IG over baseline and was persistently high during follow-up (Table 2). CCPKnow results. In both groups, clinical characteristics and beliefs affected the CCPKnow score statistically (Table 3). Statistically significant results for both groups. Differences in knowledge between groups were statistically significant in every phase of the study ( p < 0.05), which indicates that a woman in IG is more likely to have a better knowledge level. Beliefs, in both groups, did not change significantly during the study. Conclusions: CCPKnow level was enhanced and maintained in IG after one educational session statistically. Probably education in women with IBD bridges the gap between patients and healthcare providers and finally reduces the percentage of voluntary childness in IBD women.